Músicas populares y músicas de estado: sobre una versión rock del himno nacional argentino - Buch, Esteban (Sociedad y Economía, 2008)
The prominent Argentinian musician Charly Garcia produced, for scandal of many and the satisfaction of others, a “rock” version of the national anthem of his country. This text discusses this fact in the context of relationships among music, politics and society in an Argentine which was leaving behind the era of military dictatorships at the end of the twentieth century.